Using a Participatory Research Approach in a School-Based Physical Activity Intervention to Prevent Diabetes in the Hualapai Indian Community, Arizona, 2002–2006 - Teufel-Shone, Nicolette I.; Gamber, Michelle; Watahomigie, Helen; Siyuja, T. J.; Crozier, Laurie; Irwin, Sandra L. (Preventing chronic disease, 2014)
In the United States, type 2 diabetes has reached epidemic proportions among indigenous people. Community-based participatory research offers American Indian communities and university partners an opportunity to integrate skills in community action and systematic inquiry to develop locally acceptable primary prevention interventions to combat diabetes risk factors. The Hualapai Tribe and the University of Arizona designed, implemented, and assessed a school-based physical activity intervention to reduce diabetes risk factors among youth. During a 2-year period, trained community members led in-school physical activity classes 2 times per week among students in grades 3 through 8. Body mass index (BMI), fitness measures, and fasting blood glucose level were measured on 6 occasions. Descriptive statistics and t tests were used to assess change in outcome measures. Of the more than 100 youth who took part in the physical activity classes for 2 years, 71 youth (38 male, 33 female) participated in 3 or more data collection sessions. Over time, the percentage of youth with a high fasting blood glucose level of more than 125 mg/dL decreased concurrently with significant improvements in fitness measures. However, BMI increased in both male and female participants. The high number of youth who missed more than 3 data collection sessions was attributed to poor school attendance and tardiness. Classes led by lay physical activity leaders can affect diabetes risk factors in youth. Incongruous health and fitness outcomes suggest that one indicator does not adequately define the risk profile; BMI alone may not be sufficient as a measure of diabetes risk in youth.